Clinical Outcomes of Endoscopic Ultrasonography–Guided Pancreatic Cyst Ablation. Issue 6 (July 2016) - Park, Joo Kyung; Song, Byeong Jun; Ryu, Ji Kon; Paik, Woo Hyun; Park, Jin Myung; Kim, Jaihwan; Lee, Sang Hyub; Kim, Yong-Tae
Abstract : Objectives: Endoscopic ultrasonography–guided ethanol ablation therapy for pancreatic cystic lesions is a minimally invasive treatment but still is an experimental therapy. The aims were to investigate the safety and efficacy of endoscopic ultrasonography–guided ethanol ablation therapy. Methods: The inclusion criteria were the following: clinically indeterminate pancreatic cystic lesions in radiologic imaging studies, 2 to 5 cm unilocular or oligolocular cysts without communication to main pancreatic duct, and patients with high-risk operation. Results: There were 91 study patients with median follow-up of 40 months. The response rate was as follows: complete resolution, 41 (45%); partial resolution, 37; and persistent cysts, 13. Pancreatic cystic lesions were categorized based on cystic fluid analysis: 9 intraductal papillary mucinous neoplasms (IPMNs), 12 mucinous cystic neoplasms, 33 serous cystic neoplasms, and 28 uncategorized cysts. The success rate was significantly different according to cystic fluid analysis (serous cystic neoplasm, 58%; mucinous cystic neoplasm, 50%; IPMN, 11%; uncategorized cysts, 39%; P < 0.0001). There were 3 patients with mild pancreatitis after the treatment. Conclusions: Endoscopic ultrasonography–guided ethanol ablation therapy seems to be a safe treatment modality. However, it was only effective in 11% of IPMNs. Therefore, the clinical application should be very limited for certain patients who could not tolerate the surgical treatment.